The search for new 4-amino-5-methyl-4H-1,2,4-triasole-3-thion derivatives with diuretic activity - Kravchenko, T. V.; Кравченко, Тетяна Вікторівна; Кравченко, Т. В. (Запорожский государственный медицинский университет, 2018)
1,2,4-Triazole derivatives have been widely used in medical practice due to their wide spectrum of biological activities and low toxicity, as they have 1,2,4-triazole cycle in their structure. That makes 1,2,4-triazole derivatives a very promising and attractive class of organic compounds in research of their physical and chemical properties, and biological activity determining. In order to find new substances with potential biological activity 20 new compounds of 4-amino-5-methyl-4H-1,2,4-tiazole-3-thion derivatives were synthesized, which have never been described in literature before. The objective of this study was the research of bioactivity of 4-amino-5-methyl-4H-1,2,4-tiazole-3-thion derivatives. Materials and methods. Compounds of research were synthesized in Department of Toxicological and Inorganic Chemistry of ZSMU. Berchin method was used in order to estimate the effect of compounds on excretory function of kidneys. Results. Diuretic activities of 4-amino-5-methyl-4H-1,2,4-tiazole-3-thion derivatives were studied. The compounds exhibit both diuretic and antidiuretic effects. It is worth noting that 4-((R-idene)amino)-5-methyl-4H-1,2,4-triazole-3-thion derivatives demonstrated both moderate and high diuretic activity. In such way, introduction of 3,4-methoxybenzyl, 3,5-methoxybenzyl and 2-chloro-6-fluorobenzyl substituents into the structure of 4-((R-idene)amino)-5-methyl-4H-1,2,4-triazole-3-thion slightly increased diuretic effect. Reduction of compounds 4-((4-bromobenzylidene)amino)-5-methyl-4H-1,2,4-triazole-3-thion, 5-methyl-4-((thiophen-2-ylmethylene)amino)-4H-1,2,4-triazole-3-thion, 4-((2-chloro-6-fluorobenzylidene)amino)-5-methyl-4H-1,2,4-triazole-3-thion caused decline of diuretic activity. The most potent bioactivity was observed in 4-((4-methoxybenzyl)amino)-5-methyl-4H-1,2,4-triazole- 3-thion. Conclusion. Derivatives of 4-amino-5-methyl-4H-1,2,4-tiazole-3-thion exhibit both diuretic and antidiuretic effects. “Structure – еffect” relation was shown. The most potent activity was observed in 4-((4-methoxybenzyl)amino)-5-methyl-4H-1,2,4-triazole-3-thion. Похідні 1,2,4-тріазолу широко застосовують у медичній практиці завдяки великому спектру біологічної дії та низькій токсичності, що зумовлено наявністю в їхній структурі тріазольного циклу. Цей факт робить особливо перспективним і цікавим дослідження фізико-хімічних і біологічних властивостей цього класу органічних сполук. Для пошуку нових потенційно біологічно активних речовин синтезували 20 нових сполук, які раніше не описані у фаховій літературі, – похідні 4-аміно- 5-метил-4H-1,2,4-тріазол-3-тіонів. Мета роботи – дослідження діуретичної активності похідних 4-аміно-5-метил-4Н-1,2,4-тріазол-3-тіонів. Матеріали та методи. Сполуки синтезували на кафедрі токсикологічної та неорганічної хімії ЗДМУ. Для встановлення впливу сполук на екскреторну функцію нирок використовували метод Є. Б. Берхіна. Результати. Дослідили діуретичну активність похідних 4-аміно-5-метил-4Н-1,2,4-тріазол-3-тіонів. Вони проявляють як діуретичний, так антидіуретичний ефект. Досліджуючи діуретичну дію 4-((R-іден)аміно)-5-метил-4H-1,2,4-тріазол-3-тіонів, слід відзначити, що вони виявляють помірний і високий діуретичний ефект. Так, введення в молекулу 4-((R-іден)аміно)-5- метил-4H-1,2,4-тріазол-3-тіону 3,4-метоксибензилового, 3,5-метоксибензилового та 2-хлор-6-фторбензилового радикалу призводить до незначного посилення діуретичного ефекту. Відновлення сполук II, III, IX призводить до послаблення діуретичної дії. Найбільш активним є 4-((4-метоксибензил)аміно)-5-метил-4H-1,2,4-тріазол-3-тіон. Висновки. Похідні 4-аміно-5-метил-4Н-1,2,4-тріазол-3-тіонів проявляють як діуретичний, так і антидіуретичний ефект. Встановили взаємозв’язок «структура – дія». Найбільш активною сполукою є 4-((4-метоксибензил)аміно)-5-метил-4H- 1,2,4-тріазол-3-тіон. Производные 1,2,4-триазола получили широкое применение в медицинской практике благодаря значительному спектру биологического действия и низкой токсичности, что обусловлено наличием в их структуре триазольного цикла. Этот факт делает особенно перспективным и интересным исследование физико-химических и биологических свойств данного класса органических соединений. Для поиска новых потенциально биологически активных веществ синтезировали 20 новых соединений, ранее неописанных в специализированной литературе, – производные 4-амино-5-метил-4H-1,2,4-триазол-3-тионов. Цель работы – исследование диуретической активности производных 4-амино-5-метил-4Н-1,2,4-триазол-3-тионов. Материалы и методы. Исследуемые соединения были синтезированы на кафедре токсикологической и неорганической химии ЗГМУ. Для установления влияния соединений на экскреторную функцию почек использовали метод Е. Б. Берхина. Результаты. Исследована диуретическая активность производных 4-амино-5-метил-4Н-1,2,4-триазол-3-тионов. Они проявляют как диуретический, так антидиуретический эффекты. При исследовании диуретического действия 4-((R-иден) амино)-5-метил-4H-1,2,4-триазол-3-тионов следует отметить, что они проявляют умеренный и высокий диуретический эффект. Введение в молекулу 4-((R-иден)амино)-5-метил-4H-1,2,4-триазол-3-тиона 3,4-метоксибензилового, 3,5-метоксибензилового и 2-хлор-6-фторбензилового радикала приводит к незначительному усилению диуретического эффекта. Восстановление соединений II, III, IX приводит к снижению диуретического действия. Наиболее активным является 4-((4-метоксибензил)амино)-5-метил-4H-1,2,4-триазол-3-тион. Выводы. Производные 4-амино-5-метил-4Н-1,2,4-триазол-3-тионов проявляют как диуретический, так и антидиуретический эффект. Установлена взаимосвязь «структура – действие». Наиболее активным соединением является 4-((4-метоксибензил)амино)-5-метил-4H-1,2,4-триазол-3-тион.
Пошук нових діуретичних речовин серед похідних 4-аміно-5-метил-4H-1,2,4-тріазол- 3-тіону
Поиск новых диуретических веществ среди производных 4-амино-5-метил-4H-1,2,4- триазол-3-тиона
Keywords: 1,2,4-triazole; diuretic effect; derivatives of 4-amino-5- methyl-4H-1,2,4- triazole-3-thion; 1,2,4-тріазол; діуретичний ефект; похідні 4-аміно-5- метил-4H-1,2,4- тріазол-3-тіонів; 1,2,4-триазол; диуретический эффект; производные 4-амино-5-метил-4H-1,2,4- триазол-3-тионов